Providing Help in Europe: Are In-Household Care and Outside-Household Support Associated With Grandparental Child care? - Savela, Roosa-Maria; Coall, David A.; Danielsbacka, Mirkka; Tanskanen, Antti O. (SAGE Publications, 2026)
Grandparental child care is a vital form of social support that can enhance family well-being.
Prior studies have found that older adults who provide support to one individual are more likely
to offer help to others within their families and social networks. However, little research has
examined whether helping others is associated with grandparental child care. Using data from the
Survey of Health, Aging and Retirement in Europe, covering 27 countries, and using multinomial
regression models, we show that (a) support provided to individuals outside the household is
associated with increased grandparental child care, whereas (b) family care provided within the
household is not. The findings are further discussed with particular attention to their societal
implications.